THE DUAL MODEL OF THE DEVELOPMENT OF GERMAN ARMED FORCES - A. Yu. Timofeev (Vestnik MGIMO-Universiteta)
At the present stage Germany seeks to increase its influence at the international arena and plays active role in the solution of the problems in the sphere of inter-national security. In this regard Germany uses a wide range of foreign policy tools, some of them are military. The Bundeswehr becomes the armed forces which are intended for the usage at the global level and for the solution a large range of tasks, including ones which are atypical for the period of the «cold war». The reform of the Bundeswehr led to its real division of German armed forces into two components. The first of them were the forces which were intend-ed for the usage outside NATO zone of responsibility, and the second component were troops which should complete the tasks of the ensuring the territorial de-fense of Germany and its Alliance`s partners if necessary. In the 1990s – 2000s years the undisputed priority was the development of forces, used outside the Euro-Atlantic society. At the same time the combat capa-bilities of another component were gradually declining in the situation of com-mon reducing the personnel and armaments of the Bundeswehr. At the present stage the Western countries came to a period of profound deterioration of rela-tions with Russia and faced with the increasing manifestations of the non-traditional security threats caused by instability in the Middle East and North Af-rica. It puts Germany in front of necessity of simultaneous development of both parts of the armed forces. In this regard in the conclusion there is an attempt to characterize the modern and perspective image of the Bundeswehr and to outline possible ways of overcoming the existing difficulties of its development.